1979
DOI: 10.2136/sssaj1979.03615995004300050011x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Exchange Equilibria Involving Aluminum in a Kaolinitic Ultisol

Abstract: Cation exchange equilibria in an acid Ultisol profile involving K‐Al, Ca‐Al, K‐Ca, Na‐K, and Na‐Ca exchanges were studied. Selectivity coefficients, surface activity coefficients and free energy changes were computed using the thermodynamic formulations.In exchange equilibria involving Al, the magnitude of selectivity coefficients Kc, was affected by pH, surface composition, and hydrolysis of Al. In equilibria not involving Al, good reversibility for K‐Ca, Na‐K and Na‐Ca exchanges was obtained. Potassium was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
11
1
1
Order By: Relevance
“…Udo (1978) reported a preference for K + by the exchanger phase to Ca 2+ in soils from western Nigeria dominated by kaolinite. In kaolinitic Ultisols from western Nigeria, Pleysier et al (1979) found a selectivity sequence of K N Al N Ca. Seven out of nine weathered soils from Malaysia and Sri-Lanka studied by Talibudeen (1972) exhibited preference for K + over Al 3+ .…”
Section: Introductionmentioning
confidence: 92%
“…Udo (1978) reported a preference for K + by the exchanger phase to Ca 2+ in soils from western Nigeria dominated by kaolinite. In kaolinitic Ultisols from western Nigeria, Pleysier et al (1979) found a selectivity sequence of K N Al N Ca. Seven out of nine weathered soils from Malaysia and Sri-Lanka studied by Talibudeen (1972) exhibited preference for K + over Al 3+ .…”
Section: Introductionmentioning
confidence: 92%
“…The very small number of specific sorption sites in this Podosol soil can be attributed to the absence of micaceous clay minerals with an interlayered structure (e.g. illite and vermiculite), and kaolinite, which have a high affinity for K + ions (Pleysier et al 1979;Levy et al 1988;Phillips et al 1988a; Barbayiannis et al 1996;Chappell and Evangelou 2000).…”
Section: Resultsmentioning
confidence: 96%
“…Both of these sources of charge exhibit a stronger preference for multivalent cations relative to monovalent cations (e.g. Pleysier et al 1979;Phillips et al 1988a;Barbayiannis et al 1996). Therefore, the higher concentrations of organic matter and hydrous Fe and Al oxides in the 0 -30 and 30 -50 cm depth materials may explain the lower k K and k NH 4 for these materials relative to that for the >50 cm depth.…”
Section: Resultsmentioning
confidence: 99%
“…Whether this distribution pattern is a consequence of preferential adsorption of Ca 2+ or Mg 2+ to K + or a consequence of 'luxury consumption' of K + by crops is not well understood. But cation exchange studies from savanna soils of Western Nigeria indicated a preferential K + to Ca 2+ and Mg 2+ retention by the soils (Udo, 1978;Pleysier et al, 1979). A recent study by Agbenin and Yakubu (2007) also established a preferential K + adsorption to Ca 2+ and Mg 2+ in a savanna soil whose formation had been strongly influenced by volcanic activities.…”
Section: Introductionmentioning
confidence: 89%